2000
DOI: 10.1046/j.1360-0443.2000.9519510.x
|View full text |Cite
|
Sign up to set email alerts
|

The process of relapse in severely dependent male problem drinkers

Abstract: It was concluded that post-treatment self-efficacy rating is a predictor of treatment outcome and time to lapse and relapse and that cognitive functioning is a predictor of treatment outcome and time to lapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 30 publications
3
46
0
4
Order By: Relevance
“…Recently, neurocognitive disinhibition was found to be associated with the development of substance use disorders as well (Tarter et al 2004). Thus, similar neurocognitive etiologies may be involved in the development as well as the progression of and relapse in PG and substance dependence (Tapert et al 1999 ;Allsop et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, neurocognitive disinhibition was found to be associated with the development of substance use disorders as well (Tarter et al 2004). Thus, similar neurocognitive etiologies may be involved in the development as well as the progression of and relapse in PG and substance dependence (Tapert et al 1999 ;Allsop et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that a higher severity of dependence was predictive of relapse (Babor et al 1987 ;Langenbucher et al 1996 ;Simpson et al 1999 ; but see : Allsop et al 2000 ;Bottlender & Soyka, 2005). Higher levels of selfreported impulsivity are also found to be predictive of relapse and early treatment drop-out in substance dependence (Moeller et al 2001 ;Doran et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In sum, our study not only replicates the association between alcohol dependence and utilitarian moral judgment but also reveals that defective fear and disgust decoding are key predictors of utilitarian choices in personal moral dilemmas. These findings have important clinical implications, given that poor decision-making is a well-validated predictor of alcohol and drug relapse (Allsop et al, 2000;Bechara and Damasio, 2002). Furthermore, the impairments in fear and disgust recognition could be related to clinical observations in alcohol-dependent individuals, such as the lack of disgust of vomit, and poor personal hygiene (Hazelton et al, 2003;Johnson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, many drug and alcohol treatments are explicitly designed to target and improve self-efficacy (Witkiewitz & Marlatt, 2004). Broad support for the role of self-efficacy as a determinant of positive treatment outcome has been found in alcohol-and drug-dependent patients (Allsop, Saunders, & Phillips, 2000;Goldbeck, Myatt, & Aitchison, 1997;Miller & Longabaugh, 2003;Rychtarik, Prue, Rapp, & King, 1992;Stephens, Wertz, & Roffman, 1993). For example, Ilgen, McKellar, and Tiet (2005) compared measures of self-efficacy to other measures of alcohol use and psychosocial functioning; high self-efficacy was the single strongest predictor of abstinence from drug and alcohol use 1 year after treatment.…”
Section: Introductionmentioning
confidence: 98%